Protecting biodiversity outside protected areas: can agricultural landscapes contribute to bird conservation on Natura 2000 in Italy? - Cai, Mattia; Pettenella, Davide (Journal of Environmental Engineering and Landscape Management, 2013)
Even when a Protected Area (PA) is adequately managed within its boundaries, its ecological functioning may be influenced by human activities in the surrounding landscape through a number of mechanisms. This paper investigates how conservation outcomes are affected by land use change in neighboring areas on a cross-section of protected sites, the Italian portion of the EU's Natura 2000 network. We exploit variation in space to relate indicators of success of conservation efforts to measures of landscape structure. We focus on features of the landscape that pertain to agriculture because this is the dominant form of land use in many areas of the country, and the major ongoing trends in land use dynamics involve farmland. Our results suggest that the patterns and rates of land use change currently observed in Italy have the potential to result in non-negligible adverse consequences for wildlife.First published online: 14 Dec 2012